+0

# ​ Which expression is equal to (x−3)(2x2−x+3) ?

0
39
2
+435

Which expression is equal to (x−3)(2x2−x+3) ?

SamJones  Mar 1, 2018

#1
+1

just multiply x to each term in the second equation

the multiply -3 to each term in the second equation.

then combine like terms.

all answers have the same fron and last terms so what about the middle ones.

x and -x = - x^2

-3 and 2x^2 = - 6x^2

x and 3 = 3x

-3 and -x = 3x

now we know it is the last answer

Guest Mar 1, 2018
Sort:

#1
+1

just multiply x to each term in the second equation

the multiply -3 to each term in the second equation.

then combine like terms.

all answers have the same fron and last terms so what about the middle ones.

x and -x = - x^2

-3 and 2x^2 = - 6x^2

x and 3 = 3x

-3 and -x = 3x

now we know it is the last answer

Guest Mar 1, 2018
#2
0

hi how are you doing today.

Guest Mar 1, 2018

### 19 Online Users

We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  See details